White matter microstructure in body dysmorphic disorder and its clinical correlates - Feusner, Jamie (2013)
Body dysmorphic disorder (BDD) is characterized by an often-delusional preoccupation with misperceived defects of appearance, causing significant distress and disability. Although previous studies have found functional abnormalities in visual processing, frontostriatal, and limbic systems, no study to date has investigated the microstructure of white matter connecting these systems in BDD. Fourteen medication-free BDD participants and 16 healthy controls were scanned using diffusion-weighted MRI. We utilized probabilistic tractography to reconstruct tracts of interest, and tract-based spatial statistics to investigate whole brain white matter. To estimate white matter microstructure we used fractional anisotropy (FA), mean diffusivity (MD), and linear and planar anisotropy (c(l) and c(p)). We correlated diffusion measures with clinical measures of symptom severity and poor insight/delusionality. Poor insight negatively correlated with FA and c(l) and positively correlated with MD in the inferior longitudinal fasciculus (ILF) and the forceps major (FM). FA and c(l) were lower in the ILF and IFOF and higher in the FM in the BDD group, but differences were nonsignificant. This is the first diffusion-weighted MR investigation of white matter in BDD. Results suggest a relationship between impairments in insight, a clinically important phenotype, and fiber disorganization in tracts connecting visual with emotion/memory processing systems.